Food security in times of crisis: Poor developing countries are different - Michael Brüntrup (Deutsches Institut für Entwicklungspolitik (DIE), 2020)
The corona crisis has taken the world captive. While there is broad discussion of the immediate risks of the pandemic, the same can rarely be said of the immense impact that the virus is expected to have on food security for those living in absolute poverty. This impact is resulting primarily from lockdown measures aimed at reducing infection rates and is already having a detrimental effect on all four pillars of food security through many cause-and-effect chains: Access to food will deteriorate tremendously if incomes fall and purchasing power dwindles, as most likely will food availability as a result of the difficulties and losses in terms of inputs, harvests, trade and transportation. The new instability could easily spread to other areas such as migration, security and statehood. Women especially are at risk, as are children in many cases. Different types of households are affected in very different ways. The first to be hit hardest by this crisis will be households with no connection to the agricultural sector, that is, the urban poor for the most part. Those that do have agricultural links could benefit from food transfers or (partially) migrate back to their home regions. The impact of this crisis on the food situation of smallholder subsistence households, which describes most of the world's poorest families, will be smaller in the short term at least (unlike in the case of natural crises). Larger agricultural enterprises capable of producing a reliable supply of food for the market should prove to be a pillar of stability during and after the crisis, provided the markets they serve do not suffer massive collapse. At overall level, the impact of the corona crisis on nutrition, alongside the design of lockdown measures, depends in particular on the degree of economic development, the extent to which the agricultural sector is separated from the rest of the economy and the scope that the state and prosperous sectors of society have and retain for making transfers. When it comes to balancing measures to tackle the coronavirus with those for economic stimulus, greater emphasis must be placed on the economy in poorer nations than in wealthier ones. Lockdown measures pose a risk to life and health in poor countries. It should be clearly stressed at this point that the "economy" refers in this context to the complex results chains on the way to food security and not simply to growth and jobs. Corona strategies in the poor South should thus look different to those in the global North and in emerging economies. For development cooperation, this means in the first instance assisting with the development of specific local strategies. Initiatives must flexibly address awareness-raising, health and hygiene in particular in the short term and, where necessary, include cash and food transfers and employment programmes. Economic structures and actors should be protected and supported in this process. Resilience in the face of the corona epidemic and other epidemics can be boosted in the medium term by promoting sustainable agricultural and food systems in particular. In so doing, it is vital to avoid neglecting resilience with regard to other types of crisis in which other cause-and-effect chains are operating in some cases and in which other relevant measures are thus required. For instance, climate-related crises often harm the local agricultural sector, and so access to the international agricultural market serves as a key means of protection. Research shows that employing a combination of economic diversity, reserve-building, open agricultural markets, insurance policies and social security systems is the most effective way to achieve resilience across the board.
Keywords: 330